The European guilds: An economic analysis - Ogilvie, Sheilagh (Princeton Princeton University Press, 2019)
Guilds ruled many crafts and trades from the Middle Ages to the Industrial Revolution, and have always attracted debate and controversy. They were sometimes viewed as efficient institutions that guaranteed quality and skills. But they also excluded competitors, manipulated markets, and blocked innovations. Did the advantages of guilds outweigh their costs? Analyzing thousands of guilds from 1000 to 1880, The European Guilds answers that question with vivid examples and clear economic reasoning. Sheilagh Ogilvie features the voices of honourable guild masters, underpaid journeymen, exploited apprentices, shady officials, and outraged customers, and follows.